2014
DOI: 10.1039/c4nr02988g
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient graphene-based Cu(In, Ga)Se2 solar cells with large active area

Abstract: Two-dimensional graphene has tremendous potential to be used as a transparent conducting electrode (TCE), owing to its high transparency and conductivity. To date graphene films have been applied to several kinds of solar cells except the Cu(In, Ga)Se₂ (CIGS) solar cell. In this work, we present a novel TCE structure consisting of a doped graphene film and a thin layer of poly(methyl methacrylate) (PMMA) to replace the ZnO:Al (AZO) electrode for CIGS. By optimizing the contact between graphene and intrinsic Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…384 The boron-doped graphene has better conductivity and a higher work function, resulting in a PCE of 7.86%. 387 Compared with the CIGS solar cells with AZO electrodes, the devices with graphene electrodes showed a decreased reflectance and enhanced quantum efficiency in the near infrared region. 385 In 2012, they further improved the performance of CdS/CdTe solar cells by using Cu NWs-doped graphene as transparent electrodes and showed a maximum PCE of 12.1% and good thermal stability.…”
Section: Quantum Dot-sensitized Solar Cells and Other Inorganic Solarmentioning
confidence: 99%
“…384 The boron-doped graphene has better conductivity and a higher work function, resulting in a PCE of 7.86%. 387 Compared with the CIGS solar cells with AZO electrodes, the devices with graphene electrodes showed a decreased reflectance and enhanced quantum efficiency in the near infrared region. 385 In 2012, they further improved the performance of CdS/CdTe solar cells by using Cu NWs-doped graphene as transparent electrodes and showed a maximum PCE of 12.1% and good thermal stability.…”
Section: Quantum Dot-sensitized Solar Cells and Other Inorganic Solarmentioning
confidence: 99%
“…Similar to the CdTe system, graphene was first considered as an alternative front contact. Yin et al [ 48 ] first reported an effort of replacing AZO with graphene or graphene/PMMA composite. Their results showed that the direct contact between graphene and i-ZnO was poor due to surface damage during PMMA removal, which also affects carrier collection through evaporated metal grids.…”
Section: Research Progress Of Graphene-composited Thin Film Solar mentioning
confidence: 99%
“…Their results showed that the direct contact between graphene and i-ZnO was poor due to surface damage during PMMA removal, which also affects carrier collection through evaporated metal grids. Thus, they optimized the fabrication process, as shown in Figure 5 [ 48 ]. In this study, all possible CIGS solar cells have been described and the graphene has been incorporated at step-4 in all of the processes, except for standard process.…”
Section: Research Progress Of Graphene-composited Thin Film Solar mentioning
confidence: 99%
See 1 more Smart Citation
“…Copper indium gallium selenide (CIGS) thin-films solar cells are made of the compounds of chalcopyrite-type ternary, i.e., CuInS2, CuInSe2 (CIS) and CuGaSe2 (CGS), with the bandgaps of 1.5 eV, 1.0 eV and 1.7 eV, respectively [1]. The idea then came up to make a multi-alloy layer of Cu (In, Ga)(Se, S)2 belongs to the I-III-VI2 family, which together forms a CIGS absorber layer with a tunable bandgap of around 1.3-1.55 eV depending on the composition of Ga or In [2,3]. The energy conversion efficiency of over 23% has been reported for a lab-scale CIGS cell by the Chinese Academy of Sciences (ISCAS) [4,5].…”
Section: Introductionmentioning
confidence: 99%